Comparative urbanization of birds in China and Europe based on birds associated with trees - Møller, Anders Pape; Xia, Canwei; ZHou, Bo; Che, Xianli; CHu, Xingzhi; Feng, Changzhang; Laursen, Karsten; Morelli, Federico; Li, Wangming; Liu, Jianping; Quan, Qing; Zhang, Min; et al. (Current zoology, 2019)
Urbanization effects on living organisms are spatially heterogeneous. Here we quantified the abundance of birds per tree in forested urban and rural habitats for 85,829 trees mainly in China and Europe. A population model was based on the assumption that: 1) birds have a normally distributed habitat preference; 2) an increase in population size linked to the habitat preference; 3) a population size dependent on the habitat preference; and 4) the removal of a certain fraction of individuals giving rise to extinction. We tested for large-scale differences in the impact of urbanization on the frequency distribution of the difference in abundance between urban and rural habitats in China and parts of Europe. The difference in the frequency distribution of urban population density of birds in trees minus rural population density of birds in trees in China and Europe was statistically significant, suggesting that the abundance of birds differed between trees in urban and rural habitats, but more so in China than in Europe. We hypothesize that more pronounced differences in China than in Europe may have arisen due to the Four Pests Campaign in 1958-1962 that resulted in death of hundreds of millions of birds (mainly tree sparrows Passer montanus, but also numerous other less common species that were starting to become urbanized around 1960). Species that were less common in 1960 could not sustain reductions in population size in urban areas and hence these species are still rare or absent in urban areas today 60 years later.
Keywords: distribution; frequency skewness; ANOSIM; human-bird interactions; sociality; community composition; kurtosis; habitat preference